(untitled) (Research, Society and Development, 2021)
The environmental issue related to electrical and electronic waste is a widely discussed issue, especially after the establishment of the National Policy on Solid Waste- Law No. 12,305 / 2010. The study centers and universities, considered poles of technological advances, are major generators of this type of waste, so the implementation of a correct management of these electronics is essential in these places. This paper seeks to present the current reality of electronic waste management within the Federal University of Pará (UFPA), revealing scenarios of its generation in the years 2013, 2014, 2015, 2016 and 2017, in addition to showing the flaws in this management, in order to present proposals for its improvement. It was found that the largest production of electronic waste occurred in 2014, where it is possible to highlight the microcomputers that are destined to the Department of Warehousing and Heritage (DAP) at UFPA. Finally, it was shown that the biggest flaw in management is the lack of communication between the institutes and the DAP, complemented by the high bureaucracy present between the procedures, in addition to the absence of the application of shared responsibility. As points of recommendation, it was proposed to implement environmental education actions with technicians and civil servants and insert this waste in bidding processes between UFPA and cooperatives that collect and treat this type of material.